Peningkatan Keterampilan Menulis Deskripsi Tokoh Pahlawan melalui Model Pembelajaran Talking Stick Siswa Kelas IV SDN Tegalasri 4 - Nourma Oktaviarini (Jurnal Bidang Pendidikan Dasar, 2021)
The purpose of this research is to describe the application of the talking stick learning model and the improvement of writing skills. The type of research used is Classroom Action Research (PTK). The research subjects were fourth grade students of SDN Tegalasri 4, Wlingi District, Blitar Regency. The results of the research cycle I meeting 1 an average of 66 with a percentage of 45% completeness of the 29 students, meeting 2 an average of 67 with a percentage of 52% completeness. Cycle II meeting 1 total 2218 average 76 69%, Meeting 2 average 82 with percentage completeness 83%. The conclusion is that the talking stick learning model is able to improve the writing skills of a hero character description while also motivating students to learn to write and can stimulate students' creativity in expressing ideas.